Bandwidth enhancement and miniaturization of dielectric resonator antenna for 5.8 GHz WLAN applications [electronic resource] - Khalil. K. Gebril, 1984- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2010